Gene expression analysis during acute hepatitis C virus infection associates dendritic cell activation with viral clearance. Issue 5 (19th October 2015) - Zabaleta, Aintzane; Riezu‐Boj, Jose‐Ignacio; Larrea, Esther; Villanueva, Lorea; Lasarte, Juan Jose; Guruceaga, Elizabeth; Fisicaro, Paola; Ezzikouri, Sayeh; Missale, Gabriele; Ferrari, Carlo; Benjelloun, Soumaya; Prieto, Jesús; et al.
Abstract : Viral clearance during acute hepatitis C virus (HCV) infection is associated with the induction of potent antiviral T‐cell responses. Since dendritic cells (DC) are essential in the activation of primary T‐cell responses, gene expression was analyzed in DC from patients during acute HCV infection. By using microarrays, gene expression was compared in resting and activated peripheral blood plasmacytoid (pDC) and myeloid (mDC) DC from acute HCV resolving patients (AR) and from patients who become chronically infected (ANR), as well as in healthy individuals (CTRL) and chronically‐infected patients (CHR). For pDC, a high number of upregulated genes was found in AR patients, irrespective of DC stimulation. However, for mDC, most evident differences were detected after DC stimulation, again corresponding to upregulated genes in AR patients. Divergent behavior of ANR was also observed when analyzing DC from CTRL and CHR, with ANR patients clustering again apart from these groups. These differences corresponded to metabolism‐associated genes and genes belonging to pathways relevant for DC activation and cytokine responses. Thus, upregulation of relevant genes in DC during acute HCV infection may determine viral clearance, suggesting that dysfunctional DC may be responsible for the lack of efficient T‐cell responses which lead to chronic HCV infection. J. Med. Virol. 88:843–851, 2016 . © 2015 Wiley Periodicals, Inc.